Tracing carbon footprint along a supply chain using block chain technology - Liu, Tianjiao (Nanyang Technological University, 2025)
This study addresses the challenge of ensuring data transparency and trust in carbon footprint management across supply chains. Existing research highlights the limitations of traditional supply chain systems in verifying and securely managing carbon emission data, leading to trust issues between companies and their suppliers. To bridge this gap, this research designs a Carbon Footprint Management Platform (CFMPABT) that integrates blockchain and IoT technologies. The platform uses IoT sensors to collect real-time carbon emission data, while blockchain ensures data transparency, immutability, and security. This dual approach effectively addresses issues of data opacity and supplier credibility, promoting trust within the supply chain. The CFMPABT platform’s design is validated through a specific manufacturing supply chain scenario and demo, demonstrating its practical application in enhancing data transparency and trust. By providing real-time monitoring, automated data verification, and secure data sharing, the platform offers a novel solution for managing carbon data in supply chains. This study contributes to the development of sustainable supply chains by proposing an integrated technical framework that can be adapted to manufacturing industries, thus filling existing research gaps and promoting green supply chain practices. Keywords: Carbon Footprint, Blockchain, loT Technology